The predictive effect of heart rate variability on atrial fibrillation after coronary artery bypass grafting - Wanwarang Wongcharoen (2018)
Objectives: To examine the relationship between heart rate variability (HRV) and postoperative atrial fibrillation (POAF) after coronary artery bypass grafting (CABG) and to compare its relationship between on-pump and off-pump CABG. Methods: The study was a prospective cohort of 138 patients undergoing elective CABG. The patients with history of AF were excluded. The 24-hour Holter electrocardiograms were recorded before surgery to assess HRV and for 7 days after surgery to detect POAF. Results: POAF occurred in 31 (22.5%) of 138 patients. Baseline characteristics were comparable between patients with and without POAF. On-pump CABG was performed in 56.5% of patients. The significantly longer root mean square of successive differences (RMSSD) was observed in patients undergoing on-pump CABG who had POAF than those who did not (38.1±21.5 vs.31.4±26.1 ms,p=0.012). In those undergoing off-pump CABG, HRV parameters did not differ between patients with and without POAF. The area under ROC curve for RMSSD to predict AF after on-pump CABG was 0.70±0.07 (95% CI,0.57-0.83,p=0.010). The RMSSD cutpoint of >23.8 ms could predict AF after on-pump CABG with the sensitivity and specificity of 89% and 50%, respectively. Conclusion: The HRV could moderately predict AF occurrence after on-pump CABG but not off-pump CABG. These results may influence practice patterns with regard to prophylactic measures of AF in those undergoing on-pump CABG with RMSSD>23.8 ms.